2011
DOI: 10.1007/s00247-011-1998-2
|View full text |Cite
|
Sign up to set email alerts
|

Variability in imaging utilization in U.S. pediatric hospitals

Abstract: Diagnostic imaging utilization and costs vary widely in pediatric hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Prior studies evaluating the effect of insurance status on the incidence of perforated appendicitis in both children and adults have shown that the risk for perforated appendicitis is higher among patients who lack private insurance (40-42). Given that CT serves an important role in the imaging of complicated appendicitis and the evaluation of abscess formation, it patients (32,33). This research adds to emerging literature surrounding CT use in the ED, building on the earlier study by Larson et al and on the work of other authors who have documented an increase in CT use within the ED (24)(25)(26)34,35).…”
Section: Data Collection and Processingmentioning
confidence: 86%
“…Prior studies evaluating the effect of insurance status on the incidence of perforated appendicitis in both children and adults have shown that the risk for perforated appendicitis is higher among patients who lack private insurance (40-42). Given that CT serves an important role in the imaging of complicated appendicitis and the evaluation of abscess formation, it patients (32,33). This research adds to emerging literature surrounding CT use in the ED, building on the earlier study by Larson et al and on the work of other authors who have documented an increase in CT use within the ED (24)(25)(26)34,35).…”
Section: Data Collection and Processingmentioning
confidence: 86%
“…We linked patient records from ED information system and N early half (44.4%) of all emergency department (ED) visits in the United States in 2007 involved performance of an imaging test (1), and more recent data (47.2% in 2010) show no signs of abatement (2). Several studies highlighted substantial variation that exists in imaging rates across (3)(4)(5)(6)(7)(8)(9) and within (10)(11)(12) EDs. The presence of this variation suggests that at least some of the increase in the use of ED imaging may be unwarranted.…”
Section: Data Sources and Study Populationmentioning
confidence: 99%
“…However, MI use within the paediatric population remains unclear, and the few published studies found mainly provide data detailing the use of MI on paediatric populations outside of Europe before the year 2010 [22,24,40] or else solely focus on the use of a single modality such as CT [23,25,38,[41][42][43][44][45]. It is in this context that we believe that our study findings provide a valid insight into recent trends occurring at a general hospital in Fig.…”
Section: Discussionmentioning
confidence: 67%